The impact of blockchain technology on financial reporting quality: perspectives from the Kingdom of Saudi Arabia and the United Arab Emirates - Alsalmi, Noora (2025)
Blockchain Technology (BCT) has emerged as a transformative innovation beyond its initial applications in bitcoin trading, impacting sectors such as finance, accounting, and data management. Defined as a shared, distributed ledger that facilitates the documentation of transactions and monitoring of both tangible and intangible assets within a business network (Gupta, 2017), blockchain's potential to enhance Financial Reporting Quality (FRQ) remains empirically underexplored, particularly in emerging markets. This study investigates BCT's impact on FRQ within Saudi Arabia and the United Arab Emirates—regions characterized by varying stages of IFRS adoption and comprehensive regulatory efforts to enhance financial transparency. The unique economic and cultural contexts of these countries provide a distinct backdrop for exploring BCT's potential effects on financial reporting practices. Through a rigorous mixed-methods approach, the research analysed data from 235 financial and governmental professionals across both countries, balanced between blockchain adopters (41.7%) and non-adopters (58.3%), offering comprehensive perspectives on implementation challenges and benefits. This quantitative phase was enriched by 12 in-depth interviews providing detailed contextual insights into blockchain adoption and its impact on financial reporting practices. The findings demonstrate that blockchain's core features—decentralization, distributed ledger technology, immutability, consensus mechanisms, and real-time processing—significantly enhance the qualitative characteristics of financial reporting as defined by IASB. Blockchain's capability to enhance accuracy and integrity improved faithful representation, while its enhanced accessibility and precision strengthened reporting relevance. The technology's inherent standardization promoted comparability across entities, while its transparent nature enhanced verifiability through improved asset tracking and audit processes. Interview findings revealed that firm size significantly moderates these benefits, with larger organizations leveraging economies of scale more effectively, while smaller firms face distinct resource-related challenges. This research makes several significant contributions to both theory and practice. Theoretically, it advances understanding by integrating blockchain capabilities with three fundamental frameworks: agency theory, demonstrating how blockchain mitigates information asymmetries; stakeholder theory, showing enhanced stakeholder engagement through improved transparency; and Resource-Based View (RBV), revealing how firm size influences blockchain's effectiveness as a strategic resource. The study empirically validates blockchain's impact on FRQ through these theoretical lenses, extending academic discourse beyond conceptual propositions. Practically, the research provides actionable insights for organizations implementing blockchain, offering tailored strategies based on firm size and organizational context. It addresses critical implementation challenges including technological complexity, system maturity, scalability issues, privacy concerns, and infrastructure requirements. These insights are particularly valuable for policymakers and corporate managers in emerging economies navigating blockchain adoption. The study identifies several barriers to implementation, including varying levels of management awareness, regulatory compliance needs, and resource constraints. Understanding these challenges is crucial for comprehending potential obstacles affecting blockchain adoption in accounting and financial sectors. Moreover, the research provides detailed examination of the specific economic and regulatory contexts of Saudi Arabia and the UAE, offering in-depth analyses that highlight the distinct impacts of blockchain in these regions. This comprehensive investigation advances both theoretical understanding and practical application of blockchain in financial reporting, while considering the unique characteristics of emerging markets. The findings demonstrate that while blockchain significantly enhances FRQ, its effectiveness varies with organizational context and implementation approach, providing crucial insights for future research and practical application in financial reporting systems.